A Study on Some Verses Attributed to Rudaki based on a Few Old Sources - Sajjad Dehghan; Zahra Nasirishiraz; Nasrollah Emami; Mozhgan Shirmohammadi (Matn/Pizhūhī-i Adabī, 2021)
Abu Abdullah Rudaki's Divan is one of the most important poetry Divans in the Khorasan area, from which only some scattered verses have remained in the ancient texts and manuscripts. With great effort, the late Saeed Nafisi managed to collect many of Rudaki's poems from various texts and provided a brief Divan from this highly productive poet. He used such dictionaries as Saha'a al-Fors, Asadi Tussi's Loghate Fors, and also rhetorical books such as Tarjoman al-Balaghah, and al-Mu'ajm. While praising the efforts of this respected scholar, the present paper tries to unveil and remove two shortcomings in his work so as to take a further step towards a reliable version of Rudaki's poetry. The two shortcomings are as follows: first, there are verses by Rudaki in these sources that have not been recorded in Nafisi's Divan. Second, by citing the putative sources, Nafisi has attributed some verses to Rudaki, while investigations made it clear that such verses do not belong to him but to other well-known poets. Considering the importance of research in the poetry of Khorasan, especially Rudaki's poetry, it is attempted to collect verses which are not included in Nafisi's Divan, introduce new verses by Rudaki, and reject wrong attributions by referring to the printed books and several manuscripts in this paper.